PENERAPAN METODE CONTEXSTUAL TEACHING AND LEARNING DALAM PEMBELAJARAN SENI BUDAYA DI SMP - Resti Yulia Gusti; Ardipal Ardipal; Yos Sudarman (FBS Universitas Negeri Padang, 2012)
This research purpose to for describe and explain how applying of method study of CTL in study of legitimate stage. Research type qualitative with descriptive approach of analysis. Technique data collecting through book study, interview and observation. Result of this research find that study steps conducted is forming group (learning comunity). Giving modeling, question and answer (questioning), student find Iesson items (inkuiri), conducting refleksion and authentic assessment to student. Assessment taken to passing test practice to the fore class grouply, while its value is group value and individual value. Group value of one is more 90 and group value of two is 70 reaching Standard of Kopetens Learn To minimize (SKBM). kata kunci: Penerapan, CTL, Seni teater, kualitatif, deskriptif analisis